2013
DOI: 10.1027/1016-9040/a000125
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Family Relations in Luxembourg

Abstract: According to the intergenerational solidarity model, family members who share similar values about family obligations should have a closer relationship and support each other more than families with a lower value consensus. The present study first describes similarities and differences between two family generations (mothers and daughters) with respect to their adherence to family values and, second, examines patterns of relations between intergenerational consensus on family values, affectual solidarity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Also, the perspective from which one regards intergenerational relations plays a role here -parents rate their relations toward their children generally more positively than vice versa, a phenomenon which has been described by the intergenerational stake hypothesis (Bengtson & Kuypers, 1971;Birditt, Hartnett, Fingerman, Zarit, & Antonucci, 2015). With regard to intergenerational solidarity, studies have suggested a more unconditional support from the older to the younger generations whereas shared values were a more important predictor of provided support upwards the generational ladder (Albert et al, 2013;Hammarström, 2005).…”
Section: Bengtson's Solidarity Paradigmmentioning
confidence: 97%
See 2 more Smart Citations
“…Also, the perspective from which one regards intergenerational relations plays a role here -parents rate their relations toward their children generally more positively than vice versa, a phenomenon which has been described by the intergenerational stake hypothesis (Bengtson & Kuypers, 1971;Birditt, Hartnett, Fingerman, Zarit, & Antonucci, 2015). With regard to intergenerational solidarity, studies have suggested a more unconditional support from the older to the younger generations whereas shared values were a more important predictor of provided support upwards the generational ladder (Albert et al, 2013;Hammarström, 2005).…”
Section: Bengtson's Solidarity Paradigmmentioning
confidence: 97%
“…Kiilo, Kasearu, & Kutsar, 2016), the relation between other dimensions seems less unequivocal. For instance, whereas normative solidarity is often supposed to play a crucial role in support provisions, several studies have demonstrated that other aspects might be more influential in this regard, such as for instance emotional solidarity or an intergenerational consensus regarding values (Albert, Ferring, & Michels, 2013). Also, the perspective from which one regards intergenerational relations plays a role here -parents rate their relations toward their children generally more positively than vice versa, a phenomenon which has been described by the intergenerational stake hypothesis (Bengtson & Kuypers, 1971;Birditt, Hartnett, Fingerman, Zarit, & Antonucci, 2015).…”
Section: Bengtson's Solidarity Paradigmmentioning
confidence: 97%
See 1 more Smart Citation
“…A study on intergenerational support among migrant families with all family members residing in Europe points out that "intergenerational support is important throughout the individual life course and a major mechanism of cultural continuity". It contradicts a little bit what is written above -Immigration history is important (Albert et al, 2013) but then there is not much difference with the host population when it comes to support (Bordone & de Valk, 2016).…”
Section: Intergenerational Family Solidarity (Igfs) In the Context Ofmentioning
confidence: 47%
“…Empirical findings suggest that several structural factors are likely to influence intergenerational family solidarity such as immigration history and geographical proximity (Albert, Ferring, & Michels, 2013;Matias, Andrade, Fontaine, Alves, & Martinez, 2008). A study on intergenerational support among migrant families with all family members residing in Europe points out that "intergenerational support is important throughout the individual life course and a major mechanism of cultural continuity".…”
Section: Intergenerational Family Solidarity (Igfs) In the Context Ofmentioning
confidence: 99%